Effect of cow urine on the growth characteristics of fusarium lateritium, an important coffee fungus in Zimbabwe - Gotora, Timothy; Masaka, Lawrence; Sungirai, Marvelous (Hindawi Publishing Corporation, 2015)
An in vitro assay was carried out to establish if cow urine at different concentrations (500 uL/mL, 300 uL/mL, 200 uL/mL, and 100 uL/mL) can be used to control the growth of F. lateritium, the fungal agent causing Fusarium bark disease in coffee. The growth characteristics selected were conidial germination, germ tube length, mycelial growth rate, and sporulation. Copper oxychloride 50% W.P. was the standard, distilled water was the negative control, and undiluted cow urine was the positive control. The undiluted cow urine was most effective in inhibiting fungal growth with the rest of the cow urine concentrations showing dose dependent efficacy compared to the negative control (P < 0.01). Copper oxychloride had the highest efficacy of all treatments with the exception of the inhibition of mycelial growth where undiluted cow urine had higher efficacy and sporulation where efficacy was comparable to undiluted cow urine. There is potential for the use of cow urine as a means of controlling Fusarium bark disease with other advantages being availability, low cost, and limited environmental damage.